Why pay attention to paths in the practice of environmental modelling?. (June 2017) - Lahtinen, Tuomas J.; Guillaume, Joseph H.A.; Hämäläinen, Raimo P.
Abstract: Taking the 'path perspective' helps to understand and improve the practice of environmental modelling and decision making. A path is the sequence of steps taken in a modelling project. The problem solving team faces several forks where alternative choices can be made. These choices determine the path, together with the impact of uncertainties and exogenous effects. This paper discusses phenomena that influence the problem solvers' choices at the forks. Situations are described where it can be desirable to re-direct the path or backtrack on it. Phenomena are identified that can cause the modelling project to get stuck on a poor path. The concept of a path draws attention to the interplay of behavioral phenomena and the sequential nature of modelling processes. This helps understand the overall effect of the behavioral phenomena. A path checklist is developed to help practitioners detect forks and reflect on the path of the modelling project. Highlights: The steps taken in a modelling project create a path – the path can change the results. Biases and other phenomena influence modeler choices at decision forks along the path. Backtracking steps can be necessary to avoid getting stuck on a poor path. Understanding the risks of path dependence in environmental modelling is important. A path checklist helps modelers detect forks and cope with path dependence.